Effects of indigofera zollingeriana and ammonium sulfate-ca(oh)₂ as protein and non-protein nitrogen supplement on in vitro ruminal fermentation - Pertiwi, Mira Ndaru; Harahap, Muhammad Ainsyar; Achmadi, Joelal (Journal of Advanced Veterinary Research, 2025)
This study aimed to evaluate the effects of a combined protein–non-protein nitrogen (NPN) supplement based on Indigofera zollingeriana and ammonium sulfate-Ca(OH)2 on in vitro rumen fermentation characteristics. A completely randomized design was applied with five treatments, N0 (100% ammonium sulfate), ID0 (100% Indigofera), NID19 (NPN: Indigofera = 1:9), NID11 (1:1), and NID91 (9:1), with six replications. Parameters measured included ammonia (NH₃) concentration, total volatile fatty acids (TVFA), acetate, propionate, butyrate, microbial protein synthesis (MPS), dry matter degradation, total gas production, and methane production (CH₄). The NID19 treatment associated with significantly higher (P<0.05) total VFA (380.99 mM), acetate (350.87 mM), microbial protein (17.79 mg/dL), and gas production (97.67 mL), while resulting in lower NH₃ than N0. The N0 treatment exhibited the highest NH₃ (117.48 mM) but the lowest gas and methane production. The inclusion of Ca(OH)₂ in the protein–NPN supplement reduced NH₃ concentration, gas production, gas production rate, and methane output. Meanwhile, Indigofera inclusion contributed to higher microbial protein synthesis, VFA concentrations, and dry matter degradation in the rumen.